Short Synthesis of the Selective Rho-Kinase Inhibitor Y-27632 and of Its Enantiomer - Belotti, D.; Peglion, J. L.; Cossy, J. (Letters in Organic Chemistry, 2005)
Y-27632 and its enantiomer were synthesized in 8 steps from trans-1,4-cyclohexanedicarboxylic acid by using a diastereoselective reductive amination of a ketone.
Keywords: kinase inhibitor